2022
DOI: 10.1186/s12893-022-01551-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following two different techniques of an open ventral hernia repair for large hernias: a prospective randomized study

Abstract: Background We compare the health-related quality of life (QoL) of patients with incision hernias before and after surgery with two different techniques. Methods In this prospective randomized study, the study population consisted of all patients who underwent the first surgical incisional hernias repair during the 1-year study period. Patients who met the criteria for inclusion in the study were randomized into two groups: the first group consisted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Only a trend of better QoL outcomes in the laparoscopic group was observed, but scores differed not significantly. Improvement of QoL was mostly reflected in the physical subscales of the SF-36 instrument, which is in line with previous studies [ 30 ]. Better short-term QoL after laparoscopic repair has been described previously [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Only a trend of better QoL outcomes in the laparoscopic group was observed, but scores differed not significantly. Improvement of QoL was mostly reflected in the physical subscales of the SF-36 instrument, which is in line with previous studies [ 30 ]. Better short-term QoL after laparoscopic repair has been described previously [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Trials in hernia repair have consistently reported improvements in quality of life following minimally invasive techniques for abdominal wall hernia repair [27]. Our study aligns with these findings.…”
Section: Discussionsupporting
confidence: 90%
“…Trials in hernia repair have consistently reported improvements in quality of life following minimally invasive techniques for abdominal wall hernia repair [ 27 ]. Our study aligns with these findings.…”
Section: Discussionmentioning
confidence: 99%